Optical Coherence Angiographic Demonstration of Retinal Changes From Chronic Optic Neuropathies. (4th March 2017) - Chen, John J.; AbouChehade, Jackson E.; Iezzi, Raymond; Leavitt, Jacqueline A.; Kardon, Randy H.
ABSTRACT: Glaucoma causes a decrease in peripapillary perfused capillary density on optical coherence tomography (OCT) angiography. However, other chronic optic neuropathies have not been explored with OCT angiography to see if these changes were specific to glaucoma. The authors evaluated OCT angiography in 10 patients who suffered various kinds of chronic optic neuropathies, including optic neuritis and ischaemic optic neuropathy, and found that all optic neuropathies showed a decrease in peripapillary vessel density on OCT angiography, regardless of the aetiology of the optic neuropathy. The peripapillary vessel loss on OCT angiography correlated well with the areas of retinal nerve fibre layer thinning seen on OCT.